Sistem Pendukung Keputusan Pemilihan Smartphone Kelas Bawah Terbaik pada Toko Bram Cell dengan Metode Simple Additive Weighting (SAW) - Silfia Andini; Rani Anggraini; Sofika Enggari (Universitas Putra Indonesia YPTK Padang, 2021)
Bram Cell store is a store that sells various types of low-end smartphones at affordable prices. However, the problem faced by the Bram Cell Store is processing data in selecting the best low-end smartphone, because there is no special system for selecting the best low-end smartphone, so it takes a long time to determine. To overcome this problem, this research was conducted with the aim of building a Decision Support System (DSS) by applying the Simple Additive Weighting (SAW) method which is useful for simplifying the smartphone selection process. The design of a decision support system using the SAW method produces applications that perform effective and efficient selection. The impact of this research is helping Bram Cell in selecting the best low-end smartphone and minimizing selection errors used in the previous systemKeywords: Decision Support System, Weight Product, Fabric